2017
DOI: 10.1051/matecconf/20179403004
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing – a sustainable manufacturing route

Abstract: Abstract. Additive Manufacturing (AM) technologies allow developing and manufacturing very complex shaped parts and functional products with a high level of customization, being a great alternative to Traditional Manufacturing (TM) methods like injection molding, die-casting or machining. Due to the importance of cleaner production in the field of manufacturing processes, sustainability of AM processes needs to be assessed in order to make easier its acceptance and implementation in the industry. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In contrast, an investigation reported in Ref. [90] revealed that CNC machining has less ecological impact than the SLS and FDM processes. An investigation to analyse the production time and energy consumption in terms of the building orientation and internal filling in FDM, was presented in Ref.…”
Section: Energy Consumptionmentioning
confidence: 85%
“…In contrast, an investigation reported in Ref. [90] revealed that CNC machining has less ecological impact than the SLS and FDM processes. An investigation to analyse the production time and energy consumption in terms of the building orientation and internal filling in FDM, was presented in Ref.…”
Section: Energy Consumptionmentioning
confidence: 85%
“…Manufacturing process technology innovations, such as sustainable machining [77,78], sustainable lubrication and nanofluids [148], sustainable additive manufacturing [117], sustainable welding [120], sustainable casting [129], and sustainable metal forming [167], are also of paramount importance for SM and will act as "the nuts and bolts" in our journey towards SM.…”
Section: Conceptualisation and Discussionmentioning
confidence: 99%
“…Various sustainability aspects of additive manufacturing (AM) was studied, including the sustainability impact assessments of this emerging technology [113][114][115]; comparative studies against conventional manufacturing techniques [116,117]; and use of more sustainable additive manufacturing techniques [118] and materials, including performance evaluation of recycled materials [101].…”
Section: Thematic Map Of Sustainable Manufacturing Technology Researchmentioning
confidence: 99%
“…The mechanical properties of this filament material which is suitable for using with 3D printing are given in Table 1. The main reason for using PLA within the scope of the research this plastic material has more advantages than ABS [27]. PLA is a biodegradable thermoplastic polyester material derived from cleaner sources, containing less toxic and requiring lower temperatures with 3D printing, thus positively influence consumption of energy.…”
Section: Methodsmentioning
confidence: 99%